Student Mastery of Association Concept In Aceh Selatan Polytechnic Computer Engineering Program - Fera Anugreni; Muhammad Anhar Pulungan; Asmaidi (Jurnal Inotera, 2021)
Mathematical Association material becomes difficult for students to learn since it is described in the form of set-forming notation and story-based questions (applied). Moreover, they find it difficult to determine the number of subsets with several determined members. The author's observations while teaching at the South Aceh Polytechnic Computer Engineering Study Program for the 2018/2019 academic year obtained data that students did not master Discrete Mathematics subjects, especially the material of the Association. This can be seen in daily assignments, midterm exams, and final semester exams. The author as a lecturer in the Study Program was disappointed with the results obtained. The approach and type of this research is a quantitative approach and a pure experimental type of research. The research sample of the second-semester students of the South Aceh Polytechnic Computer Engineering Study Program for the 2019/2020 academic year was 16 students. The research data was the test scores collected from students. The instrument in this study was a test question. The data collection technique in this research is a written test. Data analysis used t-test at a significant level α = 0,05, dk = 4, with standard value of = 69. Based on the analysis gained and . Thus, the result turns out or 1.83 > 1,75. Thus it is concluded that the mastery of Computer Engineering Study Program students at the Polytechnic of South Aceh for the 2019/2020 academic year in understanding the set material has reached a level of success.